Metal Ions in Bio-Imaging Techniques - Sigel, Astrid (Metal Ions in Life Sciences Ser., 2021)
Metal Ions in Life Sciences links coordination chemistry and biochemistry in their widest sense and thus increases our understanding of the relationship between the chemistry of metals and life processes; in fact, it is an old wisdom that metals are indispensable for life. The series reflects the interdisciplinary nature of Biological Inorganic Chemistry and coordinates the efforts of scientists in numerous interconnecting research fields.